Validation of the Chinese version of academic goals orientation questionnaire in nursing student: a study based on SEM and IRT multidimensional models - Yuqing Li; Lei-lei Guo; Jiaofeng Gui; Xiaoyun Zhang; Ying Wang; Haiyang Liu; Jinlong Li; Yunxiao Lei; Xiaoping Li; Lu Sun; Liu Yang; Ting Yuan; et al. (BMC, 2023)
Abstract Objective To translate the Academic Goals Orientation Questionnaire (AGOQ) into Chinese and to determine the validity and reliability of the (AGOQ) in Chinese nursing students based on SEM and IRT multidimensional models. Methods The participants were 654 nursing students with an age range of 17-26 years (mean age 21.61 ± 1.73 years). The psychometric properties of AGOQ were investigated based on a dual analytical perspective of structural equation modeling (SEM) and item response theory (IRT). Results The Cronbach's α value of the questionnaire is 0.895. A four-factor model was obtained by exploratory factor analysis, which explained the variance of 71.892%. With confirmatory factor analysis, a new four-factors model was built and showed an acceptable goodness-of-fit, chi-square/degree of freedom (CMIN/DF) = 4.008, goodness of fit index (GFI) = 0.932, adjusted goodness of fit index (AGFI) = 0.905, comparative fit index (CFI) = 0.952, incremental fit index (IFI) = 0.952, Tucker Lewis index (TLI) = 0.941. In the analysis part of IRT, according to the comparison between Akek's information criterion (AIC) and Bayesian information criterion (BIC), we choose the Graded Response Model (GRM) for analysis. The results show that the difficulty value is monotonically increasing, and the discrimination of all items is greater than 0.19, which shows that 16 items can be retained. Conclusions This study tested the psychometric characteristics of AGOQ of nursing students in China. The results confirmed that the Chinese version of AGOQ has good psychometric characteristics and can be used to measure the academic goal orientation of nursing students in China.